Controlled twinning and martensitic transformation in metastable AISI D3 (X210Cr12) steel by sequential deep rolling and liquid nitrogen cooling. (September 2021) - Ehle, Lisa C.; Spille, Joshua; Meyer, Heiner; Kämmler, Jeannine; Werner, Jonas; Schwedt, Alexander; Epp, Jeremy; Weirich, Thomas E.; Mayer, Joachim
Graphical abstract: Abstract: Stainless steels like X210Cr12 consist of metastable austenite that transforms into martensite when a critical temperature or critical strain is reached. However, the mechanism of martensite formation and the shape and appearance of martensite can differ significantly depending on the used mechanical or thermal pathway. This necessitates a systematic study on the martensitic transformation and twinning of metastable austenite in X210Cr12 after liquid nitrogen cooling, deep rolling and their sequential combinations. The thereby obtained surface modifications were characterized by hardness penetration measurements, electron backscatter diffraction (EBSD), transmission electron microscopy (TEM) and orientation and phase mapping using automated scanning electron nano-diffraction (SEND). X-Ray diffraction (XRD) was performed to measure residual stresses in the surface near regions of the samples. The here obtained results show that liquid nitrogen cooling yields formation of coarse grained martensite with grain sizes between 1 and 10 μm and deep rolling causes formation of a nanosized microstructure containing martensite and twins. Moreover, the here obtained results suggest that compressive residual stresses of up to −750 MPa together with the martensite/twin nanostructure stabilizes metastable austenite and prevents the formation of large martensite grains in the surface zone during subsequent liquid nitrogen cooling. A substantial hardness increase ranging from 355 HV0.1 up to about 850 HV0.1 was measured for all treatments. The highest value of about 950 HV0.1 was measured after martensite transformation induced by liquid nitrogen cooling.